Comparative study on preliminary breakdown pulse trains observed in Johor, Malaysia and Florida, USA - Baharudin, Zikri Abadi; Noor Azlinda Ahmad; Fernando Mahendra; Jäkke Mäkelä; Vernon Cooray (Elsevier, 2012)

(untitled)
In this paper, the preliminary breakdown (PB) pulse train preceding the negative first return stroke (RS) is recorded using a broad band antenna system. These analyses were carried out in Johor Bahru, Malaysia and Florida, United States. This is a novel initiative at examining and identifying the characteristics of the PB pulse trains in the negative cloud-to-ground flashes observed in Malaysia. The arithmetic mean of the total pulse train duration is 12.3 ms and the weighted arithmetic mean of the pulse durations and interpulse intervals are 11 s and 152 s, respectively. The arithmetic mean ratio between the maximum peak amplitude of the PB pulse and the peak RS electric field was 27.8%, and the corresponding value in Florida was 29.4%. The arithmetic mean of the time duration between the most active part of the pulse train, and the RS was 57.6 ms in Malaysia and 22 ms in Florida. A qualitative comparison of our results with those obtained earlier in Sri Lanka, Sweden and Finland supports the hypothesis that the PBP/RS ratio is higher in the northern regions compared to the tropical regions.